Oral Health-Related Quality of Life: A Cross-Sectional Survey among Adult Patients in Mashhad, Iran - Fatemeh Darvishzadeh; Mojtaba Dorri; Naser Sargolzaei; Hamidreza Arab; Amir Moeintaghavi; Mahyareh Alizadeh (Mashhad University of Medical Sciences, 2013)
Introduction: Quality of life is defined as the sense of well-being and satisfaction with daily performances influenced by dental and oral conditions. Oral diseases are very common and have impacts on different aspects of individual's life and can change their performances. In other word, they can change the quality of life. The real impact of health and disease on daily performances is considered as Health-Related Quality of Life. The aim of this study was to evaluate the impacts of oral diseases on quality of life in patients referred to Mashhad Faculty of Dentistry and Jahad Dental Clinic. Methods: This cross-sectional study was performed using non randomized sampling method. For this study, 500 patients referred to Mashhad Faculty of Dentistry and Jahad Dental Clinic with age >15 years were recruited. An educated interviewer asked the questions of the Persian version of OIDP questionnaire, which was valid and reliable for Iranian population. In this index the frequency and severity of each impact were recorded. Finally, each was attributed to specific oral conditions, as indicated by the respondents. The OIDP score is expressed as the sum of the different performance scores divided by the maximum possible score. Results: According to the results of this study, 84% of patients had negative impacts on their quality of life. Gender and job had significant associations with OIDP score. There was not any significant association between OIDP score and general health. The most and the least commonly affected daily performances were eating and going out, respectively. Conclusion: The most and the least effective oral diseases were toothache and tooth size and shape, respectively so the most treatment need is root canal therapy and tooth repair and to relieve pain